(untitled) (International Journal of Food and Nutritional Sciences, 2022)
With the advancement of Science and Technology the world has become a global village and English has become a link language and an intercommunicating tongue. In order to enhance the holistic acquisition of English language it is necessary to integrate ICT (Information and Communication Technology) with the traditional method of learning and teaching English. Now a days ICT has turned into a resourceful tool for educational change and reform. With the establishment of ICT tools such as radio, TV, the internet, computer, laptop, tablets, e-books, e-learning etc in schools and colleges every student get benefited in enhancing his/her communication skills and the students find it interesting and the teaching will be interactive and lively. This paper focuses on how technology can be used in English classes to make learning more interesting and creative for students with the help of ICT.Communication Skills, E-books, E-learning, Globalization, Internet, Learning, Lingua Franca, Teaching, Technology.